Various Factors Affecting the Performance of Public Elementary School Teachers in Urban Areas (Educational Management, 2021)
This study aims to examine, identify and analyze the influence of principals' leadership and discipline on teacher performance by using the work environment as an intervening variable for elementary school teachers in urban areas scattered in Klaten Regency. Respondents of this study amounted to 124 elementary school teachers. Sampling technique usingproportional cluster random samplingand analysis techniques using path analysis (path analysis). The results of the study indicate that: 1) There is an influence of the principal's leadership on the work environment. 2) There is an influence of discipline on the work environment. 3) There is an effect of principal leadership on teacher performance 4) There is an influence of discipline on teacher performance 5) There is an influence of work environment on teacher performance 6) There is an influence of principal's leadership on teacher performance through the work environment. 7) There is an influence of discipline on teacher performance through the work environment. Based on these findings, teacher performance can be improved through improvements in principal leadership, work environment and discipline.